The allometric equations for estimating above-ground biomass in a 50 years-old secondary forest in East Kalimantan, Indonesia - KARYATI KARYATI; KARMINI KARMINI; KUSNO YULI WIDIATI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Karyati, Karmini, Widiati KY. 2023. The allometric equations for estimating above-ground biomass in a 50 years-old secondary forest in East Kalimantan, Indonesia. Biodiversitas 24: 1482-1492. Secondary forests, formed through several disturbances over the decades, have important roles in ecological and economic aspects. One of their roles in ecological aspects is the potential to store carbon. Therefore, this study aimed to develop allometric equations for estimating above-ground biomass and carbon stock in a 50 years-old secondary forest. In this field, 30 trees representing the dominant species and diameter class distribution were selected and cut down. The dry biomass of the tree's parts, including leaves, branches, and trunks, was assessed using the destructive method. The relation between trunk dry biomass and Diameter at Breast Height (DBH) showed moderate adjusted R2 value ??(0.641). Moreover, moderately strong relationships were shown by above-ground biomass with DBH (adjusted R2 of 0.516). The allometric equation to estimate above-ground biomass in 50 years-old secondary forest is useful for estimating the carbon potential in other areas of the same age, especially with a similar land use history. Information regarding biomass and carbon stock is important for forest management in general. It can assess carbon stocks, sequestration rates, and potential emissions from forests subjected to a succession process.